PENGARUH KOMPETENSI DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVINING PADA CU MAJU TARUTUNG - Munthe, Mario Nicolas; Purba, Antonius M.; Munthe, Kornel (UNIKA Santo Thomas, 2024)
This research aims to analyze and determine the influence of competence, work culture on employee performance with job satisfaction as an intervining variable at CU Maju Tarutung. Primary data was obtained through questionnaires and secondary data using documentation techniques. The total population of this study was 37 people and using a saturated sampling technique the sample was also 37 people. The data analysis technique uses multiple regression analysis, but first a validity and reliability test is carried out as well as a classical assumption test, and then a hypothesis test is carried out using the t, F and Sobel tests. The results of this research show that the competency variables, work culture together have a significant effect on job satisfaction and the competency variables, work culture and job satisfaction together have a significant effect on the performance of CU Maju Tarutung employees. Partially, the competency and work culture variables have a positive and significant effect on job satisfaction and the competency, work culture and work satisfaction variables partially have a positive and significant effect on employee performance at CU Maju Tarutung. Competence has a positive effect on employee performance which is mediated by job satisfaction, job satisfaction is not able to mediate the effect of competence on employee performance, while work culture has a positive and significant effect on employee performance and job satisfaction is able to mediate the effect of work culture on employee performance